Drivers of sovereign bond demand : the case of Japan - Ferreira, Carlos Alberto Piscarreta Pinto (2023)
The aim of this empirical paper is to understand the portfolio decisions of banks regarding their asset allocation to sovereign bonds applied to the case of Japan, over the period 2002-21. The issue is relevant because globally central banks are moving to a passive holder or even net seller stance, raising the question of whether banks can be counted among the investors which will replace them. Japan makes an interesting case since Japanese banks are among the banks in advanced economies with a larger share of non-official holdings of domestic sovereign debt, their mean ratio of gross claims on the central government to total assets is about three times above average values in the United States or in the Euro Area, and government portfolios are relatively more homogeneous. We contribute to the existing literature by exploring the impact of unconventional monetary policy on sovereign bond bank demand and putting to test the significance of risk on banks´ asset portfolio decisions using a dynamic rather than a static setting. Our results show that banks struggling to grow, more diversified, better capitalized, or larger banks during expansion periods tend to hold relatively fewer sovereign bonds. On the contrary, past higher profitability, higher economic volatility and funding risk encourage relatively greater holdings. Though less clearly, data also suggests that banks facing weaker loan performance and regional banks with more significant need of collateral hold a higher proportion of sovereign bonds. Quantitative and Qualitative Monetary Easing had a major disruptive effect over banks’ government bond demand. Excess reserves at the Bank of Japan became a low risk/low return alternative to government bonds, as banks with relatively higher excess reserves have relatively less government bond holdings in their assets. Going forward, only a reversion of the monetary base expansion may help government bonds regain their role of the single riskless asset for Japanese banks.